2017
DOI: 10.3847/1538-4357/835/1/94
|View full text |Cite
|
Sign up to set email alerts
|

Chirality and Magnetic Configurations of Solar Filaments

Abstract: It has been revealed that the magnetic topology in the solar atmosphere displays hemispheric preference, i.e., negative/positive helicity in the northern/southern hemisphere, respectively. However, the strength of the hemispheric rule and its cyclic variation are controversial. In this paper, we apply a new method based on filament drainage to 571 erupting filaments from 2010 May to 2015 December in order to determine the filament chirality and its hemispheric preference. It is found that 91.6% of our sample o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(15 citation statements)
references
References 66 publications
2
9
0
4
Order By: Relevance
“…Thus, the magnetic chirality is left-handed for AR 10930 and right-handed for AR 11158. (Note that this definition of chirality for vector magnetic field in solar ARs is consistent with the chirality definition in literature for solar chromospheric filaments, see e.g., Ouyang et al 2017. ) The chiral characteristics of ARs can be quantitatively indicated by the signs of force-free factor α of the coronal magnetic field.…”
Section: Chirality Of the Magnetic Fields In The Two Active Regionssupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, the magnetic chirality is left-handed for AR 10930 and right-handed for AR 11158. (Note that this definition of chirality for vector magnetic field in solar ARs is consistent with the chirality definition in literature for solar chromospheric filaments, see e.g., Ouyang et al 2017. ) The chiral characteristics of ARs can be quantitatively indicated by the signs of force-free factor α of the coronal magnetic field.…”
Section: Chirality Of the Magnetic Fields In The Two Active Regionssupporting
confidence: 88%
“…Flare activity was also discovered on the solar-type stars other than the Sun (Schaefer et al 2000;Benz & Güdel 2010;Shibata & Magara 2011;Maehara et al 2012;Notsu et al 2013;Shibayama et al 2013;Balona 2015;Davenport 2016). Solar flares commonly come from solar active regions (ARs), and the magnetic configuration of flare-bearing ARs is one key aspect for understanding the initiation and evolution of solar flares (e.g., Chen et al 2012;Sun et al 2015;Jiang et al 2016Jiang et al , 2018Liu et al 2016;Cheng et al 2017;Guo et al 2017;Hao et al 2017;Inoue et al 2018) and other related eruptive phenomena in the solar atmosphere (e.g., Zhang et al 2012;Ouyang et al 2017;Wang et al 2017;Liu et al 2018). The non-potential property of the magnetic fields with electric current permeating inside is believed to be the critical aspect related to the activity level of ARs (e.g., Wang et al 1996;Leka & Barnes 2003;Schrijver 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the magnetic structures of filaments have been explained as a flux-rope configuration or a sheared-arcade configuration, in which magnetic dips were believed to provide upward support against gravity (Guo et al, 2010;Chen, Harra, and Fang, 2014;Yang et al, 2016a;Ouyang et al, 2017). Although no solid observational evidences showed that one of them outdoes the other, the twisted flux rope had been widely adopted in numerous formation models of solar filament/prominence.…”
Section: Introductionmentioning
confidence: 99%
“…The long-term variations of solar magnetic structures driven by the magnetic field evolution have been monitored systematically, and there is a statistical imbalance in the occurrence of magnetic activity indicators on both hemispheres when averaged over a certain time scale ranging from a year to a solar cycle (Yan et al, 2008;Xie et al, 2012;Ouyang et al, 2017). This phenomenon is known as the north-south asymmetry of solar activity, and the existence of the hemispheric asymmetry in different solar activity indicators observed in the solar atmosphere is well known.…”
Section: Introductionmentioning
confidence: 99%